Barriers to green human resources management (GHRM) implementation in developing countries. Evidence from Ghana. (15th March 2022) - Tweneboa Kodua, Lois; Xiao, Yuchun; Adjei, Nana Osae; Asante, Dennis; Ofosu, Bright Okyere; Amankona, David
Abstract: Recent developments on climate change and sustainability have led regional and international environmental activists to exert pressure on firms to adopt and implement sustainable green initiatives. Implementation of green policies is, however, not free from obstacles. This research investigated the critical barriers to green human resource management (GHRM) implementation among Ghanaian firms. Seventeen barriers were identified and subsequently categorized into five major barriers. An interview was conducted with twenty human resource and environmental management professionals to pre-test the survey items. Later, one hundred and nineteen questionnaires were administered to selected chief executive officers (19), human resource managers (30), chief financial officers (30), and heads of employees (40) in selected firms. The Preference selection index (PSI) method was applied to rank the major barriers and sub-barriers. The economic barrier accounted for 23.3% of GHRM hindrances in the study area. Overall, the lack of financial resources scored (0.999), and emerged as the most critical barrier within the sub-barriers. The political and regulatory barrier (20.1%) came second, while the culture and education barrier (18.2%) ranked lowest. To mitigate the most critical barriers, the government and financial institutions can provide funding opportunities in the form of low-interest loans to organizations to design and implement green corporate policies and strategies. This paper adds to the existing green human resource management literature by investigating and analyzing GHRM implementation barriers within a developing country setting. This provides policy makers and practitioners with knowledge in designing suitable policies to counter environmental innovation obstacles and thereby promote GHRM implementation in Ghana and in similar economies.